Signaling Pathways That Mediate Alveolar Macrophage Activation by Surfactant Protein A and IL-4 - García-Fojeda, Belén; Minutti, Carlos M.; Montero-Fernández, Carlos; Stamme, Cordula; Casals, Cristina (Frontiers in Immunology, 2022)
Activation of tissue repair program in macrophages requires the integration of IL-4/IL-13 cytokines and tissue-specific signals. In the lung, surfactant protein A (SP-A) is a tissue factor that amplifies IL-4Ralpha-dependent alternative activation and proliferation of alveolar macrophages (AMs) through the myosin18A receptor. However, the mechanism by which SP-A and IL-4 synergistically increase activation and proliferation of AMs is unknown. Here we show that SP-A amplifies IL-4-mediated phosphorylation of STAT6 and Akt by binding to myosin18A. Blocking PI3K activity or the myosin18A receptor abrogates SP-A´s amplifying effects on IL-4 signaling. SP-A alone activates Akt, mTORC1, and PKCζ and inactivates GSK3alpha/beta by phosphorylation, but it cannot activate arginase-1 activity or AM proliferation on its own. The combined effects of IL-4 and SP-A on the mTORC1 and GSK3 branches of PI3K-Akt signaling contribute to increased AM proliferation and alternative activation, as revealed by pharmacological inhibition of Akt (inhibitor VIII) and mTORC1 (rapamycin and torin). On the other hand, the IL-4+SP-A-driven PKCζ signaling axis appears to intersect PI3K activation with STAT6 phosphorylation to achieve more efficient alternative activation of AMs. Consistent with IL-4+SP-A-driven activation of mTORC1 and mTORC2, both agonists synergistically increased mitochondrial respiration and glycolysis in AMs, which are necessary for production of energy and metabolic intermediates for proliferation and alternative activation. We conclude that SP-A signaling in AMs activates PI3K-dependent branched pathways that amplify IL-4 actions on cell proliferation and the acquisition of AM effector functions.